Bacterial Community Composition in the Growth Process of Pleurotus eryngii and Growth-Promoting Abilities of Isolated Bacteria - Chen, Liding; Yan, Miao; Qian, Xin; Yang, Ziwei; Xu, Yanfei; Wang, Tianjiao; Cao, Jixuan; Sun, Shujing (Frontiers in Microbiology, 2022)
The effects of biological factors on the vegetative growth process of mushrooms remain largely unexplored. We investigated the bacterial community in different growth stages of Pleurotus eryngii by high-throughput sequencing technology to explore the relationship between interacting bacteria and the growth and development of P. eryngii. We found significant variances in mushroom interacting association bacteria (MIAB) compositions among the samples from different growth stages, and 410 genera were identified. The bacteria in the full-bag and post-ripe stages were shifted to the biocontrol and growth-promotion ones. The mushroom growth-promoting bacteria (MGPB) were also isolated successfully and identified as B. cereus Bac1. The growth speed and density of mycelial pellets of P. eryngii, and activities of two exoenzymes (laccase and amylase), were analyzed by adding the different volumes of cell-free fermentation broth of B. cereus Bac1 to fungal culture media. The results showed that when a 5 mL cell-free fermentation broth was used, the growth speed of P. eryngii hyphae was enhanced by 1.15-fold over the control and reached 0.46 mm/h. The relative activity of laccase and amylase was increased by 26.9% and 43.83%. Our study revealed that the abundant interacting bacteria coexist with P. eryngii hyphae. Moreover, the abundance of some bacteria exhibiting a positive correlation with the growth periods of their host fungi can effectively promote the growth of the host, which will provide technical supports on the high-efficiency production of P. eryngii in factory cultivation.